منطلقات القراءة النسقية للتراث النقدي والبلاغي عند جابر عصفور - عبد الرحمان عبد الدايم (université msila, 2022)
تعددت القراءات النسقية للتراث النقدي والبلاغي العربي واختلفت حسب الخلفيات المعرفية لأصحابها، ومن بين هذه القراءات قراءة جابر عصفور للتراث النقدي والبلاغي، هذه القراءة اتسمت بالنسقيّة والإحاطة والشمول. من هذا المنطلق، تسعى هذه الدراسة إلى البحث في المستويات العلائقية في فعل القراءة عند جابر عصفور، باعتبار أنّ هذه المستويات هي منطلقاته في قراءته النسقية للتراث. There are many systematic readings of the Arab critical and rhetorical heritage and differed according to the knowledge backgrounds of their owners, and among these readings is Jaber Asfour’s reading of the critical and rhetorical heritage, this reading was characterized by systematization, briefing and comprehensiveness..From this point of view, this study seeks to investigate the relational levels in the act of reading according to Jaber Asfour, considering that these levels are his starting points in his systematic reading of heritage.
Keywords:  القراءة النسيقيّة ;  النقد ;  البلاغة ;  systemic reading ;  criticism ;  rhetoric